On the eccentricity evolution of massive black hole binaries in stellar backgrounds - Bonetti, Matteo; Rasskazov, Alexander; Sesana, Alberto; Dotti, Massimo; Haardt, Francesco; Leigh, Nathan W. C.; Arca Sedda, Manuel; Fragione, Giacomo; Rossi, Elena (Monthly notices of the Royal Astronomical Society. Letters, 2020)
ABSTRACT. We study the dynamical evolution of eccentric massive black hole binaries (MBHBs) interacting with unbound stars by means of an extensive set of thre